(untitled) (Italian Review of Legal History, 2018)
After the experiences of National Socialism and Fascism, Western Europe increasingly turned to the classical constitutional state, fundamental rights and the ideal of the constitutional state, most recently Spain and Portugal. After 1990 the individual states of the former Soviet empire followed. At the same time, however, European integration dissolved the traditional framework of the nation-state. Although a European constitution has emerged in recent decades, its impact on integration is weak. At the same time, globalization is making land borders disappear in part. Goods and services, information, data and finances lose their old ties to the territories. This changes the role of the national constitutional state, even though it is still solely responsible for the basics. New transnational forms of the constitutional state are missing or still unusual. Developing them is a key task for the next generation.